CD4CD8αα IELs: They Have Something to Say - Zhou, Chao; Qiu, Yuan; Yang, Hua (Frontiers in Immunology, 2019)
The intraepithelial lymphocytes (IELs) that reside within the epithelium of the intestine play a critical role in maintaining the immune balance of the gut. CD4CD8αα IELs are one of the most important types of IELs, and they play an irreplaceable role in maintaining the balance of the intestinal immune system. CD4CD8αα IELs are often regarded as a special subtype of CD4+ IELs that can express CD8αα on their cytomembrane. Hence, CD4CD8αα IELs not only have the ability to modulate the functions of immune cells but also are regarded as cytotoxic T lymphocytes (CTLs). Transcription factors, microbes, and dietary factors have a substantial effect on the development of CD4CD8αα IELs, which make them exert immunosuppression and cytotoxicity activities. In addition, there is an intimate relationship between CD4CD8αα IELs and inflammatory bowel disease (IBD), whereas it is still unclear how CD4CD8αα IELs influence IBD. As such, this review will focus on the unparalleled differentiation of CD4CD8αα IELs and discuss how these cells might be devoted to tolerance and immunopathological responses in the intestinal tract. In addition, the role of CD4CD8αα IELs in IBD would also be discussed.